Comparisons between heat pipe, thermoelectric system, and vapour compression refrigeration system for electronics cooling. (5th January 2019) - Liang, Kun; Li, Zhaohua; Chen, Ming; Jiang, Hanying
Highlights: Heat pipe and thermoelectric models are validated by experimental results. The thermoelectric system appears to work best at a voltage of 10 V. The heat pipe improved the cooling capacity of the thermoelectric system by 53%. VCR system is capable of dissipating much higher heat flux (200 W/cm 2 ). Two-stage TE system can be used for cooling devices at lower temperatures. Abstract: Passive systems such as air for electronics cooling have now effectively reached their limits. This paper evaluated three comparable systems for electronics cooling, including heat pipe (HP, passive system), thermoelectric (TE) and vapour compression refrigeration (VCR) systems (active systems). Mathematical model has been built for the heat pipe and the thermoelectric system respectively. Measurements have been conducted to validate the model and to compare the performance among a HP, a single stage TE system and a two-stage TE system, a combination of the HP and the TE system, and a VCR system using an oil-free linear compressor. Close agreements between the modelling and measurements have been achieved in terms of electric power input and cooling capacity at various temperatures. The HP improved the cooling capacity and the coefficient of performance (COP) of the TE system by 53% and 42% respectively at a cold end temperature of 10 °C. Heat pipe is more attractive for cooling large devices at higher temperatures. Two-stage TE system can be used for cooling devices at lower temperatures. VCR system is capable of dissipating much higher heat flux (200 W/cm 2 ) at lower temperature than all other technologies.